2009
DOI: 10.4103/0970-0358.59284
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriology of the burn wound at the bai jerbai wadia Hospital for children, Mumbai, India-A 13-year study, Part I-Bacteriological profile

Abstract: Aim:To study which organisms were prevalent in our burn unit and their antibiotic sensitivity pattern in brief.Method:Microbiological data of 1534 patients admitted to the burns unit of the Bai Jerbai Wadia Hospital for Children, Mumbai over a period of 13 years (1994-2006) was reviewed retrospectively. A total of 9333 swabs were cultured and antibiotic sensitivities to the isolated organisms determined. The age group of patients admitted to our facility ranged from one month to 15 years.Result:Klebsiella was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…A study carried out by Navendu et al in 2006 showed that 35.75% of Pseudomonas aeruginosa among infected burns patients, which is almost similar to present study [8]. A study carried out by Heggers et al in USA in 1998 showed that 51% of the burns patients are having infection of Pseudomonas aeruginosa, which has higher rate of infection as compare to present study [9].…”
Section: Discussionsupporting
confidence: 75%
“…A study carried out by Navendu et al in 2006 showed that 35.75% of Pseudomonas aeruginosa among infected burns patients, which is almost similar to present study [8]. A study carried out by Heggers et al in USA in 1998 showed that 51% of the burns patients are having infection of Pseudomonas aeruginosa, which has higher rate of infection as compare to present study [9].…”
Section: Discussionsupporting
confidence: 75%
“…Some previous studies have reported S. aureus as the predominant isolate from wounds 33,34. On the other hand, Srinivasan et al35 and Forson et al36 detected K. pneumoniae and P. aeruginosa as the predominant organisms, respectively. This difference, in predominance, may have resulted from variation in the applied treatment practices.…”
Section: Discussionmentioning
confidence: 91%
“…cephalothin, carbeniciilin, ceftazidime (100%), and cephalexin (98%) respectively [7]. According to the study of Saha et al, it is most sensitive to beta lactams -imipenem (98.72%), followed by aztreonam (33.44%) and ceftazidime (38.32%) [8].…”
Section: Resultsmentioning
confidence: 99%